การนำเสนอรูปแบบสถาบันฟุตบอลสำหรับสโมสรฟุตบอลอาชีพในประเทศไทย - สมบัติ เกตุสม (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
The purposes of this study were to propose the model of football academy for professional football clubs in Thailand. Integrated research methodology between descriptive research and futures research by technique EDFR (Ethnographic Delphi Futures Research) on the basis of current information and to study the components of the model resulted in football academy for setting the model of professional football clubs in Thailand and England. The process in research had 6 steps: 1) study of the current situation for the model of football academy for professional football clubs in Thailand for identified framework, 2) drafting the model, 3) development of model, 4) consensus group, 5) discuss for feasibility study in focus group and 6) adjustment and proposed model. The data sources derived from group of experts, administrators. group of scholars, and football experienced group, Datas were collected by using questionnaires, Interviews and focus group data. By analyzing the content, obvious frequency, median, mode and inter-quartile range. The research results showed that: The propose the model of football academy for professional football clubs in Thailand which appropriate to the context of Thailand. This study consisted of 4 main parts: 1) Statement of the problems 2) Objectives 3) Structured 4) Operations including: purpose, management, budget, facilities and accommodations, staffing requirements, players, registration, development courses pathway, knowledge andก learning programme, education and welfare and developing and linking with network and 4) Key success factors.